Characterizing the tensile behavior of double wire-feed electron beam additive manufactured "copper-steel" using digital image correlation - Kibitkin, Vladimir; Vorontsov, Andrey; Osipovich, Kseniya S.; Shamarin, Nikolay N.; Chumaevskii, Andrey V.; Rubtsov, Valery E.; Moskvichev, Evgeny N.; Savchenko, Nikolai L.; Kolubaev, Evgeniy A. (Metals)
The paper presents the results of the evaluation of the mechanical characteristics of samples of multi-metal “copper-steel” structures fabricated by additive double wire electron beam method. The global and local mechanical characteristics were evaluated using uniaxial tensile tests and full-field two-dimensional digital image correlation (DIC) method. DIC revealed the peculiarities of the fracture stages: at the first stage (0.02<ε≤0.08) the formation of V-shaped shear lines occurs; at the second stage (0.08<ε≤0.15) transverse shear lines lead to the formation of a block structure; at the third stage (0.15<ε≤0.21) the plasticity resource ends in the central part of the two necks cracks are formed, and the main crack is the cause of the fracture of the joint. It is found that shear lines are formed first in copper and then propagate to steel. Electron microscopy proves that uniformly distributed iron particles could always be found in the “Fe-Cu” and “Cu-Fe” interfaces. Additionally, the evolution of average strain rates and standard deviations were measured (calculated) in the regions of necks in copper and steel regions. New shear approach shows that the most of angles for parallel shears components are ±45°, rupture angles are about 0°, and combined account of these two types of shears provides us additional discrete angles.